The Concept of Statement of Heirs to Support Legal Certainty in Indonesia - Udin Nasrudin (Magister Kenotariatan Universitas Pasundan, 2020)
With regard to the concept of the statements of heirs to provide legal certainty, the notary is the only person authorized to draft the statements of heirs for all Indonesian citizens regardless of their classes. It is based on the UUJN (Law on the Role of Notaries) which states that notaries are authorized to establish evidence in the form of authentic deeds, including the statements of heirs. Notaries are legally established as the only officials or institution which is authorized to create the statements of heirs for all Indonesian people contained in Article 15 paragraph (1) of UUJN, on the authority of notaries to make authentic deeds. The position of Notary has its own authority, and the position itself must have legal rules, as a limitation so that the office can run well and not conflict with the authority of other positions. Making an heir's statement by a notary for all Indonesian citizens without any discrimination is in line with the concept of state law, and fulfills the legal certainty and equality before the law. Likewise, the notary's authority in making evidence as an heir or an heir's statement is also protected by UUJN, a step in line with Development Law Theory.